The proteasome inhibitor bortezomib enhances ATRA-induced differentiation of neuroblastoma cells via the JNK mitogen-activated protein kinase pathway. - Peihua Luo (Public Library of Science (PLoS), 2011)
Neuroblastoma (NB) is the most common extracranial solid tumor in childhood. Differentiated human NBs are associated with better outcome and lower stage; induction of differentiation is considered to be therapeutically advantageous. All-trans retinoic acid (ATRA) has been shown to induce the differentiation of neuroblastoma (NB) cell lines. The proteasome inhibitor bortezomib inhibits cell growth and angiogenesis in NBs. Here, we investigated the synergistic effect between bortezomib and ATRA in inducing NB cell differentiation in different NB cell lines. Bortezomib combined with ATRA had a significantly enhanced antiproliferative effect. This inhibition was characterized by a synergistic increase in neuronal differentiation. At the same time, the combination therapy showed little neuronal toxicity which was assessed in primary cultures of rat cerebellar granule cells by the MTT assay, PI staining. The combination of bortezomib and ATRA triggered increased differentiation through the activation of proteins, including RARα, RARβ, RARγ, p-JNK and p21, compared with ATRA treatment alone. Using JNK inhibitor SP600125 to block JNK-dependent activity, the combination therapy-induced neuronal differentiation was partially attenuated. In addition, p21 shRNA had no effect on the combination therapy-induced neuronal differentiation. The in vivo antitumor activities were examined in human NB cell xenografts and GFP-labeled human NB cell xenografts. Treatment of human NB cell CHP126-bearing nude mice with ATRA plus bortezomib resulted in more significant tumor growth inhibition than mice treated with either drug alone. These findings provide the rationale for the development of a new therapeutic strategy for NB based on the pharmacological combination of ATRA and bortezomib.